Mekanisme Penerapan Small Claim Court untuk Menyelesaikan Perselisihan Bisnis Akibat Wanprestasi sebagai Solusi Bisnis Cepat dan Murah - Franjes Tampubolon (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
Breach of contract disputes with small claim values are often hindered by the lengthy and costly conventional litigation process. To address this issue, the Supreme Court issued PERMA No. 2 of 2015, which was later amended by PERMA No. 4 of 2019 concerning Small Claims Court. This study aims to examine the mechanism for resolving breach of contract disputes through small claims and its effectiveness in achieving the principles of fast, simple, and low-cost litigation. This research uses a normative legal method to analyze the relevant legal procedures and regulations. The findings show that small claims court is effective in streamlining the litigation process, with a resolution time limit of a maximum of 25 working days, much faster compared to regular litigation, which can take much longer. However, the implementation of this mechanism is limited by the requirement that evidence must be simple, which can be a challenge in some cases. Thus, small claims court can be an efficient and affordable solution for business disputes with low claim values.